Effectiveness of quality of chief integrity officer, ethical climate on the level of ethics and integrity in the Malaysian federal - Asmawati, Sajari; Hasnah, Haron; Ishak, Ismail (Penerbit Universiti Malaysia Pahang, 2019)
The purpose of this quantitative study is to examine the relationship between level of ethics and integrity with Quality of Chief Integrity Officer (independence, competence, work performance) and ethical climate in the Malaysian public-sector organizations. Out of 128 questionnaires that was emailed to CIOs in the Federal level, 83 questionnaires were received and usable. The results of this study showed that the Quality of CIO (competence, work performance) and ethical climate is significantly related to the level of ethics and integrity of the public sector in Malaysia. CIO need to perform their roles such as coordinating and monitoring programs and report any breaches of integrity without fear and favour. To nurture a good ethical climate in the organization, clear policies, guideline and code of conduct should be established in all government ministries, department and statutory body in the public sector. Non-ethical conduct should be reprimanded, good ethical behavior should be rewarded accordingly and should be evident to all in the organization. The overall score of level of ethics and integrity is 79.30%, which shows that the Malaysian public sector is at “seeing ethics and integrity systematically and having a robust approach”.